Entrepreneurial Development. - Desai, Vasant (Himalaya Pub. House, 2009)
Entrepreneurship has come of age in India. While passionate entrepreneurs have always created successes, the enablers now available in the form of capital, ready talent, and fast growing markets, are making entrepreneurship the aspiration of a wide variety of people. Hence, entrepreneurial development is in the forefront of discussion and learning. The success of India`s liberalization and opening up has been built by individual entrepreneurs and companies, which have grown at a dazzling pace. Of course Government`s role in huge infrastructure investments cannot be underestimated either. From.